Reimagining movement: Dr.-ing. Masria Mustafa's mission to engineer safer, smarter and more sustainable transport systems - UiTM, Fakulti Kejuruteraan Awam (Faculty of Civil Engineering, 2025)
Assoc. Prof. Dr.-Ing. Masria Mustafa is not merely navigating roads-she is reshaping how Malaysia and the wider region envision mobility. With a doctorate in Civil Engineering from the distinguished Technical University of Munich (TUM), Germany and extensive academic experience across Australasia and Europe, she is a leading figure in transportation engineering at Universiti Teknologi MARA (UiTM). Her passion lies in teaching and guiding students, while also being actively involved in research and projects related to traffic engineering, transport planning and sustainable mobility. She remains committed to contributing to the development of better, more efficient transport systems for Malaysia and the region